2014
DOI: 10.1016/s1995-7645(14)60291-1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity and total phenolic contents in hydrophilic extracts of selected Bangladeshi medicinal plants

Abstract: The results of the present study implies that the analyzed plants possess varying degree of antioxidant capacity and, therefore, the antioxidant potency of these underused plants may be utilized to prevent oxidative damage and oxidative stress related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 19 publications
1
34
2
1
Order By: Relevance
“…So it could be concluded that the antioxidant potential of extracts rich in free aglycone forms of phenols was principally attributed to their redox properties, which allowed them to act as F I G U R E 1 Trend in percentage increase in total phenolic contents (TPC), free radical scavenging activity (FRSA), and ferric ion reducing antioxidant power (FRAP) of fermented lupin prepared from non-germinated and germinated seeds reducing agents, donors of hydrogen and quenchers of radicals. In the previously reported literature, the antioxidant capacity of different plant foods is proportional to their TPCs (Alali et al, 2007;Amzad Hossain & Shah, 2015;Tukun et al, 2014), however, this correlation was found weaker in the current study which might be due to the possible interaction of reducing amino acids and peptides with Folin-Ciocalteu reagent (Medina, 2011). In fact, these amino acids and small size peptides are formed after fermentation with microorganisms (Ruth Nazaretha Sandessy et al, 2018).…”
Section: Tpc and Antioxidant Potentialcontrasting
confidence: 67%
“…So it could be concluded that the antioxidant potential of extracts rich in free aglycone forms of phenols was principally attributed to their redox properties, which allowed them to act as F I G U R E 1 Trend in percentage increase in total phenolic contents (TPC), free radical scavenging activity (FRSA), and ferric ion reducing antioxidant power (FRAP) of fermented lupin prepared from non-germinated and germinated seeds reducing agents, donors of hydrogen and quenchers of radicals. In the previously reported literature, the antioxidant capacity of different plant foods is proportional to their TPCs (Alali et al, 2007;Amzad Hossain & Shah, 2015;Tukun et al, 2014), however, this correlation was found weaker in the current study which might be due to the possible interaction of reducing amino acids and peptides with Folin-Ciocalteu reagent (Medina, 2011). In fact, these amino acids and small size peptides are formed after fermentation with microorganisms (Ruth Nazaretha Sandessy et al, 2018).…”
Section: Tpc and Antioxidant Potentialcontrasting
confidence: 67%
“…It has been reported that polyphenolic compounds significantly constitute the active substances in these plants having multiple biological activities both in vitro and in vivo [4] In Algeria, more than 600 species of medicinal and aromatic plants are employed commonly in the practice of traditional medicine, and only a few have been studied phytochemically and evaluated for their biological activity. Rubus fruticosus (Rosaceae) and Zizhyphus vulgaris (Rhamnaceae) are used in the Algerian folkl medicine for hundreds of years as antidiarrheal, anti-inflammatory, local antalgic, warmer and urinary antiseptic [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It also contains glycosides, flavonoids, saponins and tannins (3) and has water extractable phytochemicals of medicinal importance. The total phenolic content (TPC) and trolox equivalent antioxidant capacity (TEAC) of alligator weed and the contents were 0.56±0.03 mg GAE/g FW and 0.14±0.00 µmol TE/g FW, respectively (4). It has great potential for phytoremediation (5,19,20).…”
Section: Introductionmentioning
confidence: 99%